Baeyer-Villiger oxidation with peracid generated in situ by CaLB-CLEA catalyzed perhydrolysis - Chávez, Georgina; Hatti-Kaul, Rajni; Sheldon, Roger A.; Mamo, Gashaw (Journal of Molecular Catalysis B: Enzymatic, 2013)
Candida antarctica lipase B, immobilized as cross linked enzyme aggregates (CLEAs) was used to mediate the Baeyer-Villiger oxidation of cyclohexanone to epsilon-caprolactone, and the reaction was compared with the one using Novozym (R) 435 as catalyst. The conversion was dependent on the initial concentration of cyclohexanone, and was about 90% after 48 h at concentrations of up to 0.25 M but was decreased at higher concentrations. Caprolactone concentrations up to 0.6 M had no effect on the reaction efficiency. Among the cyclic ketones tested, the highest degree of conversion was achieved for cyclopentanone (88%) and the lowest for cyclooctanone (about 2%). The effect of methyl substitution and position of substitution on the cycloketone was studied using methylcyclohexanone and it has shown to influence the conversion efficiency. Both hydrogen peroxide and the reaction by-product acetic acid had a deleterious effect on the stability of the biocatalyst. (C) 2012 Elsevier B.V. All rights reserved.